Pretreatment of the urethral mucosa at the tip of the prostate: a retrospective review in preventing stress urinary incontinence after thulium laser enucleation of the prostate - Liao, Yunfeng; Wu, Yuting; Zou, Junrong; Huang, Ruohui; Xia, Wei; Yuan, Yuanhu; Xiao, Rihai; Wang, Xiaoning; Wu, Gengqing; Zou, Xiaofeng; Zhang, Guoxi (Frontiers in Surgery, 2024)
Objective. Explore the clinical application value of urethral mucosal pretreatment at the tip of the prostate in preventing stress urinary incontinence(SUI) after thulium Laser enucleation of the prostate(ThuLEP).Methods. Eighty-seven patients with benign prostatic hyperplasia treated with ThuLEP from June 2021 to December 2022 were divided into 2 groups. Among them, 42 patients in group A underwent conventional ThuLEP and 45 patients in group B were enucleated after pretreatment of the urethral mucosa. At the tip of the prostate, pretreatment of the urethral mucosa consisted of pushing the gland separately on both sides at the level of the verumontanum, and cutting off the mucosa near the external urethral sphincter clockwise and counterclockwise.The perioperative and postoperative follow-up indicators(operation time, hemoglobin reduction, complication, Qmax, IPSS, QoL, PVR) of the two groups of patients were collected and compared. All patients were followed up 1 month after surgery.Results. All the 87 procedures were successfully completed. There was no significant difference in age and gland size between the two groups(P>0.05). There was no significant difference in operating time and hemoglobin reduction in the two groups(P>0.05). The Qmax, IPSS, QOL, PVR were significantly improved postoperatively in both groups(P<0.05).Temporary stress urinary incontinence(SUI) occurred in both groups, of which 12 cases(28.5%) in group A and 3 cases(6.7%) in group B, with a significant difference(P<0.05).There was no significant difference in the incidence of infection and urethral stricture between the two groups(P>0.05).Pretreatment of the urethral mucosa before ThuLEP for BPH significantly reduces the incidence of SUI occurring after surgery. This technique which preconditions the apical urethral mucosa of the prostate has safe and effective effect, with low complications, is worthy of clinical application.